Awareness about laryngopharyngeal reflux disease among Chinese otolaryngologists: a nationwide survey - Chen Zhao; Liang Tang; Ting Chen; Hui Yang; Xiong Chen; Xiaobo Cui; Li Shi; Xiangping Li; Jian He; Xiaoxia Peng; Shuifang Xiao; Jinrang Li; et al. (BMJ Open)
Objectives This study aimed to investigate the status of the current knowledge about laryngopharyngeal reflux disease (LPRD) among Chinese otolaryngologists.Design Multi-centre cross-sectional survey.Setting 220 medical centres in different regions of China.Participants A total of 2254 otolaryngologists from 220 medical centres in China who were successfully on-site surveyed between November 2019 and December 2020.Main outcome measures Awareness about LPRD included knowledge about risk factors, symptoms, laryngoscope signs, related diseases, current diagnostic methods and treatments.Results The percentage of participants who had heard of LPRD was 96.4%, with academic conferences as the most common source of information (73.3%). The most commonly known risk factor, symptom, laryngoscope sign, related disease, diagnostic method and treatment were alcohol consumption (44.0%), pharyngeal foreign body sensation (66.9%), hyperaemia (52.4%), pharyngolaryngitis (54.8%), pH monitoring (47.6%) and medication (82.1%), respectively. Only 28.3% of all participants knew that 24 h pH or multichannel intraluminal impedance pH monitoring was the most accurate diagnostic test. As many as 73.1% of all participants knew that proton pump inhibitors were the first-line treatment drugs. An analysis of the overall status of awareness using a scoring system suggested that otolaryngologists were better aware owing to more access, working at 3A hospitals, and postgraduate or above educational background (all p<0.05).Conclusion Although the majority of Chinese otolaryngologists had heard of LPRD, their overall awareness about the disease was not encouraging. More efforts are needed to increase the knowledge about LPRD among this group of physicians.Trial registration number ChiCTR1900025581